2015
DOI: 10.1093/femspd/ftv111
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis: metabolic adaptation and biofilm formation in response to different oxygen concentrations

Abstract: Staphylococcus epidermidis has become a major health hazard. It is necessary to study its metabolism and hopefully uncover therapeutic targets. Cultivating S. epidermidis at increasing oxygen concentration [O2] enhanced growth, while inhibiting biofilm formation. Respiratory oxidoreductases were differentially expressed, probably to prevent reactive oxygen species formation. Under aerobiosis, S. epidermidis expressed high oxidoreductase activities, including glycerol-3-phosphate dehydrogenase, pyruvate dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 98 publications
1
31
0
Order By: Relevance
“…1). As expected from previous respiratory chain protein expression results (Uribe-Alvarez et al 2016), the ability of cells to consume oxygen was proportional to [O 2 ] in the growth medium. In aerobic conditions and in the presence of lactate the rate of oxygen consumption was 70 natgO (mg prot.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…1). As expected from previous respiratory chain protein expression results (Uribe-Alvarez et al 2016), the ability of cells to consume oxygen was proportional to [O 2 ] in the growth medium. In aerobic conditions and in the presence of lactate the rate of oxygen consumption was 70 natgO (mg prot.…”
Section: Resultssupporting
confidence: 85%
“…Biofilm generation was measured in sterile Costar 96-well polystyrene plates as previously reported (Calà et al 2015;Uribe-Alvarez et al 2016). Briefly, in each well, 0.4% crystal violet in 33% glacial acetic acid was mixed with the indicated, inhibitors sodium cyanide (NaCN) (100 µM), butane-1,4-bisphosphate (B1,4BP) (1 mM) or, carbonyl cyanide m-chlorophenyl hydrazone (CCCP) (0.1, 0.5, or 1 µM, as indicated).…”
Section: Biofilm Formation and Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence included the following findings: (i) the deletion of GI prfC greatly impaired the ability of 11900 to form robust pellicle-type or attached biofilms; (ii) the displacement of GI prfC by the ICE also resulted in the reduced ability of 11900 to form robust pellicle-type or attached biofilms and (iii) the expression of oxidoreductase genes and the thioesterase gene in 11900 was significantly induced during pellicle formation. It has been reported that oxidoreductase genes affect biofilm formation of Staphylococcus epidermidis and Streptomyces gandocaensis via the respiratory chain or compound synthesis (Park et al, 2016;Uribe-Alvarez et al, 2016). The role and regulation of the oxidoreductase genes and the thioesterase gene in GI prfC during biofilm formation of 11900 require further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Gels were run for about an hour at 15 mA/gel in a Bio‐rad electrophoresis chamber. In‐gel NADH‐NBT oxido‐reductase (100 μg protein), succinate‐NBT oxido‐reductase (150 μg protein), cytochrome c oxidase (100 μg protein), and in‐gel ATPase (100 μg protein) activities were done as reported previously (Uribe‐Alvarez et al., ). 20 μg protein of solubilized Bovine Heart Mitochondria (BHM) were loaded in each gel as controls.…”
Section: Methodsmentioning
confidence: 99%